Metal-organic hybrid metamaterials for spectral-band selective active terahertz modulators - Yoo, Hyung Keun; Cho, Soo Bin; Park, Sae June; Ahn, Yeong Hwan; Kang, Chul; Hwang, In Wook; Lee, Joong Wook (Applied Sciences (Switzerland), 2021)
Optically controlled spectral-band selective terahertz (THz) modulators based on metal-organic hybrid metamaterials were investigated. An artificially structured material, which consists of two single split-ring resonators put together on the split gap side, was patterned on a silicon substrate to generate frequency-selective properties. An active layer of an organic thin film (fullerene derivative [6,6]-phenyl-C61-butyric acid methyl ester, also called PCBM) was deposited on the metamaterial-silicon structure for modulating the transmission of incident THz radiation. The metal-organic hybrid metamaterials enabled active control of spectral bands present in the transmission spectra of THz waves. In addition, the changes in the photo-excited carrier density due to the transfer of charges between the layers were quantitatively analyzed by simulation results.
Keywords: Active optics; Metamaterials; Modulators; Terahertz spectroscopy